DIGITAL LITERACY FOR GENERATION Z IN THE ERA OF SOCIETY 5.0 - Febriani, Hanura; Afriani, Zelvia Liska (STKIP Siliwangi, 2025)
Technological developments in society have encouraged the formation of a new era, namely society 5.0, where digital technology is inherent in humans, specifically in generation Z. This study aims to analyze the digital literacy levels of generation Z in learning English and examine the relationship between digital literacy competency and academic success in English. It also explores effective strategies for teachers to enhance digital literacy among students to improve their learning outcomes in the classroom. A sequential explanatory mixed-method approach was used, involving senior high school students and teachers in Bengkulu City. Data collection combined questionnaires to assess students' digital literacy competencies and in-depth interviews using the think-aloud protocol technique to gather qualitative insights. The data were analyzed using an independent sample T-test to examine the correlation between digital literacy and academic success. The findings reveal that students in senior high schools in Bengkulu have good digital literacy skills in English learning. Furthermore, the correlation analysis indicates that higher digital literacy proficiency positively affects students' success in learning English. In addition, teachers have employed some strategies to increase generation Z's proficiency with digital literacy to improve the success of English learning in the classroom.